The restrictions imposed upon the urban development by the piezometric level. Case study: Otopeni-Tunari-Corbeanca - Daniel Constantin Diaconu; Daniel Peptenatu; Adrian Gabriel Simion; Radu-Daniel Pintilii; Cristian-Constantin Draghici; Camelia Teodorescu; Alexandra Grecu; Andreea Karina Gruia; Ana-Maria Ilie (Urbanism. Arhitectura. Constructii, 2017)
The objective of the study is to identify the urban development pressure exerted upon the limits imposed by the depth of the phreatic level. The territorial systems from the vicinity of Bucharest registered a momentous dynamics and it enabled the expanding of urbanized areas beyond the limits imposed by the natural conditions. The present research involved the creation of a database concerning the depth of the phreatic level, as well as the identification of the expansion stages undertaken by the urbanized areas. There were applied questionnaires concerning the degree of knowledge regarding the development restrictions for the beneficiaries of built spaces. The spatial layout of the indicators which were used in the research permitted the discovery of some areas where the decision to build something had been taken without analyzing the low depth of piezometric level.